The Impact of Cooperative Learning: Make a Match Approach on Learning Outcomes the Quran Hadith - Hidayati, Nur; Mei, Nining Yus; Nuraiman, Nuraiman; Irayanti, Irma; Asril, Zainal (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2023)
Improving the quality of learning is a major concern in the context of modern education. One approach that has received attention is the cooperative learning model, which emphasizes interaction between students and group-based learning. In the context of the Quran Hadith subjects, the effectiveness of cooperative learning models, especially the make-a-match type, has not been fully explored. In fact, this research aims to investigate the direct impact of implementing the make a match type cooperative learning model on student learning outcomes at Madrasah Tsanawiyah. This research uses quantitative methods with an experimental approach, data sources were obtained from 44 respondents. The results of this research can conclude that the cooperative learning model of the make-a-make type has a significant effect on the learning outcomes of the Quran Hadith at Madrasah Tsanawiyah. The average post-test results show that learning using the make a match type cooperative learning learning model has better learning outcomes, based on tests using the independent sample T-Test with a significance of 5% or 0.05 analysis with the help of SPSS 24.0. The results of calculations using the independent sample T-Test obtained 0.004<0.05 with a significance level of 0.05 or 95% which states that they accept Ha and reject H0. So it can be concluded that the make-a match type cooperative learning learning model has a significant effect on the learning outcomes of the Quran Hadith at Madrasah Tsanawiyah.